Anaphylaxis with black radish - Özdemir, Öner; Dikici, Ümmügülsüm (Alergologia Polska - Polish Journal of Allergology, 2025)
Individuals performing complementary and alternative medicine applications with different mixtures used for recurrent upper respiratory tract infections and chronic cough in children, especially in winter, should be very careful. In our case report, we present the case of consuming black radish due to chronic cough, who had anaphylaxis due to black radish allergy. A 5-year-old male patient presented with complaints of urticaria, persistent vomiting, and coughing after consuming a black radish cure about 2 months ago. Approximately 4 h after the third dose of the black radish cure, red, itchy, raised skin (urticarial) lesions developed on the face and trunk, and the patient began to vomit and cough. His complaints, which lasted for half an hour, disappeared over time and the family did not go to the emergency service. In the literature, there are few adult case reports describing root vegetable allergy and anaphylaxis. Our pediatric case is the first patient having anaphylaxis described due to a black radish cure in the literature. It is an important preventive medicine duty to inform families well in terms of unpredictable allergic reactions in alternative medicine applications prepared with different foods.